If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5z + -1) + -2(z + 5) = 3(z + 1) Reorder the terms: 4(-1 + 5z) + -2(z + 5) = 3(z + 1) (-1 * 4 + 5z * 4) + -2(z + 5) = 3(z + 1) (-4 + 20z) + -2(z + 5) = 3(z + 1) Reorder the terms: -4 + 20z + -2(5 + z) = 3(z + 1) -4 + 20z + (5 * -2 + z * -2) = 3(z + 1) -4 + 20z + (-10 + -2z) = 3(z + 1) Reorder the terms: -4 + -10 + 20z + -2z = 3(z + 1) Combine like terms: -4 + -10 = -14 -14 + 20z + -2z = 3(z + 1) Combine like terms: 20z + -2z = 18z -14 + 18z = 3(z + 1) Reorder the terms: -14 + 18z = 3(1 + z) -14 + 18z = (1 * 3 + z * 3) -14 + 18z = (3 + 3z) Solving -14 + 18z = 3 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. -14 + 18z + -3z = 3 + 3z + -3z Combine like terms: 18z + -3z = 15z -14 + 15z = 3 + 3z + -3z Combine like terms: 3z + -3z = 0 -14 + 15z = 3 + 0 -14 + 15z = 3 Add '14' to each side of the equation. -14 + 14 + 15z = 3 + 14 Combine like terms: -14 + 14 = 0 0 + 15z = 3 + 14 15z = 3 + 14 Combine like terms: 3 + 14 = 17 15z = 17 Divide each side by '15'. z = 1.133333333 Simplifying z = 1.133333333
| 2.8=-0.9+y | | 15=6y-3y | | a-3=-20 | | s=3m+3z | | x^4+3x^2=4 | | 9y=-2(y+1) | | 9x-42=2x | | 8y-15y+7= | | -2(-4z)=64 | | 3x+7y= | | 2(5z)=-80 | | 10b^2-8b-7=0 | | x+43=38 | | -11m+6m=11-31 | | -5(3p+4)-25=3(2p+6) | | 2(c-6)=3(c-7) | | 8-6n+2n=43-95 | | 2y-4(2y+4)=-4-2(-1-y) | | 2(0)+6=y | | (2x+4)(5x-6)= | | 29=5-3h | | 4*-3+7= | | 4*-3=7 | | 2(5z-1)-5(z+2)=2(z+1) | | 5+2n-4=5n+2-2n | | -14=-7t | | 10p-11=-2p+7 | | 3.5q-2.7-3.9q=-1.4q-5.2 | | 2(3x-4)-(2x-4)= | | 45-23=x | | 25x-30x-16=0 | | -16-9-2= |